Predicted lifetime therapy benefit guided treatment effectively reduces residual cardiovascular risk in patients with symptomatic atherosclerotic disease. (25th November 2020) - Hageman, S.H.J; Dorresteijn, J.A.N; Bots, M.L; Asselbergs, F.W; Mosterd, A; Westerink, J; Visseren, F.L.J
Abstract: Background: Identification of patients who benefit most from further risk factor lowering may help to effectively reduce residual risk of cardiovascular disease (CVD) in patients with symptomatic atherosclerotic disease. Using the previously published SMART-REACH model, the lifetime benefit of preventive therapy can be estimated, defined as the increase in CVD-free life expectancy from preventive therapy. Purpose: To model the effectiveness of blood pressure lowering, lipid lowering and antithrombotic therapy guided by predicted lifetime benefit rather than guideline based risk factor levels in patients with symptomatic atherosclerotic disease in terms of total gain in CVD-free lifetime and events avoided. Methods: For all patients with symptomatic atherosclerotic disease in the UCC-SMART cohort (1996–2018), two treatment strategies were compared. The predicted lifetime benefit-guided treatment strategy was based on individual estimation of gain in CVD-free life as estimated with the SMART-REACH model. A lifetime benefit threshold of >1 year additional CVD-free life per therapy was deemed worthwhile for this analysis. Therapies were selected using a stepwise algorithm resembling clinical practice.In the risk factor-based strategy all patients were treated according to the most recent ESC guidelines for patients at very high risk: treatment goal LDL-c <1.8 mmol/l, systolic blood pressure <140 mmHg and antithrombotic medication. Outcomes were assessed using the SMART-REACH model in combination with relative treatment effects of the prescribed therapies. Results: In total, 7697 patients were included with coronary artery disease, cerebrovascular disease or peripheral artery disease. Treatment according to lifetime benefit would lead to an increase of 25, 388 CVD-free lifeyears (95% CI 24, 936–25, 824), threshold-based treatment to an increase of 18, 912 CVD-free lifeyears (95% CI 18, 469–19, 360). In the next 10 years and lifetime, 617 events (37%; 95% CI 36–37) and 1, 250 (32%; 95% CI 32–33) could be avoided with lifetime benefit-based treatment and 532 (32%; 95% CI 31–32) and 989 (25%; 95% CI 25–26) with risk factor-based treatment. When treating according to lifetime benefit, more therapies would be started in younger patients, which leads to a decreased incidence of CVD in younger patients (Figure 1). In patients older than 75, the incidence of CVD was higher when treating according to lifetime benefit. Conclusions: Residual risk reduction guided by lifetime benefit estimation results in more CVD-free lifeyears and more CVD events avoided compared to the conventional risk factor-based strategy. Treatment according to lifetime benefit may prevent events in younger patients. Although this requires a longer duration of preventive treatment, the potential gain in CVD-free life expectancy is substantial. Benefit-based treatment is an effective strategy for reducing residual CVD risk in patients with clinical manifest vascular disease. Funding Acknowledgement: Type of funding source: Public hospital(s). Main funding source(s): UMC Utrecht